COST SAVINGS AND BREAK-EVEN POINT OF SOLAR CELL INSTALLATION IN URBAN THAILAND - Vanlisuta, Chanchai; Makul, Natt (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the total cost and break-even point for the installation of solar cell panels on residential buildings are calculated based on real-life electric power data and compared to those calculated via data collected using various data collection methods, such as electricity bills. The number of solar panels required to provide a 7-story residential building with electric power is as follows: 1,089 panels of 75 W solar cells, 681 panels of 120 W solar cells, 545 panels of 150 W cells, and 327 units of 250 W solar cells. The number of required solar cells calculated based on the electricity bill sources indicates that 518 panels of 75 W solar cells, 324 panels of 120 W solar cells, 259 panels of 150 W solar cells, and only 156 units of 250 W solar cells are required. The comparison of the total cost of installing solar panels on the roofs of four residential buildings of various sizes showed that the discrepancy between the two costs calculated via the two methods was 110.52 % and that the break-even point was four years and 10 months. This data helps inform those interested in installing solar cells for power production.